A.S. Puškin u &laquo ; sjećanjima&raquo ; Marine Cvetajeve (Moj Puškin) - Benčić, Živa (Array, 2000)
Marina Cvetaeva wrote a narrative prose work My Pushkin in France in 1937 to commemorate the hundredth anniversary of the poet's death. Written in the form of autobiographical memories the work is distinctly set off from occasional essayistic writing then prevailing in emigration circles. In this article the author attempts firstly to enlighten the reasons that prompted Marina Cvetaeva to present Pushkin from an ultimately subjective and inner perspective such as only the autobiographical memory of the proper childhood can offer, i.e. the reasons that made her use rather introspection than the spirit of collective memory (as understood by M. Halbwachs), which has taken hold of the Russian emigration in the jubilee-year of 1937. Secondly the article analyses the work itself and the mechanism of the autobiographical memory by Cvetaeva herself, which may account for the fact that Cvetaeva's presentation of Pushkin was so different from the stereotypes taken for granted in the emigration community. The peculiar quality of Cvetaeva's Pushkin as &laquo ; impulsive&raquo ; and &laquo ; rebellious&raquo ; person is derived from the fact that what Cvetaeva is interested in her work are only those aspects of her childhood perception of Pushkin that are in accordance with her present state, which is to say with her self-appreciation, emotional states and convictions, as well as with her myth of the poet and poetic creativity in general.